Possible Futures All at Once: Time Frame and Time Lag in Short-Term Longitudinal Media Effects Research on Well-Being - Klingelhoefer, Julius; Gilbert, Alicia; Adrian, Christoph; Meier, Adrian (2025)
When assessing media effects, we seldomly consider how they change over time. Especially with the prevalence of smartphone use as short-term, fragmented media use, a systematic approach to temporal dimensions is crucial, particularly to understand mixed effects of smartphone use on well-being. We employ a multiverse approach to assess the influence of two central temporal dimensions in short-term longitudinal research: Time frame and time lag. We combine mobile experience sampling (T1 = 2,859, T2 = 7,708) and log data (K1 = 71,807, K2 = 259,004) from N1 = 84 and N2 = 192 participants. Building on theorizing on time in media effects research, we propose four patterns of how short-term effects unfold: they may follow processes of ephemerality (fleeting effects), inertia (delayed onset), or reversal (changing directions) – or there are no changes over time. We discuss theoretical implications and give practical recommendations for future studies, especially short-term longitudinal design
https://cris.fau.de/converis/publicweb/Publication/333591890
Keywords: experience sampling; media effects; multilevel; multiverse analysis; short-term longitudinal designs; time; well-being